Light and Laser Modalities in the Treatment of Cutaneous Sarcoidosis: A Systematic Review - Ana Luiza Lima; Steven Goetze; Tanja Illing; Peter Elsner (Medical Journals Sweden, 2018)
Sarcoidosis is a systemic non-caseating granulomatous disease of unknown aetiology. Cutaneous manifestations are present in approximately 10-30% of the patients with the systemic form. Therapy is indicated in case of disabling symptoms, organ dysfunction or cosmetically distressing manifestation. Despite different therapeutic possibilities, cutaneous sarcoidosis remains exceptionally difficult to treat. Light and laser therapy may be a promising alternative. In this systematic review, we summarised the available treatments according to the literature concerning light and laser therapy for cutaneous sarcoidosis. Publications written in English and German, published between January 1990 and July 2016 in the database PubMed, MEDLINE, Embase, and Scopus were analysed. Light therapy with intense pulsed light, photodynamic therapy, and ultraviolet A light therapy, as well as laser therapy with pulsed dye laser, YAG laser, and Q-switched ruby laser were described. The results are based on individual case reports and small case series. Randomised controlled studies are lacking.